Kinetics of In-111-Platelets in the Baboon: I. Isolation and Labelling of a Viable and Representative Platelet Population - Kotzé, H F; Lötter, M G; Badenhorst, P N; Heyns, A du P (Thrombosis and Haemostasis, 1985)
A fully representative and viable platelet population was isolated from the blood of 15 baboons by a multiwash procedure, and labelled with In-lll-oxine. The recovery of the total platelet population in the circulation was 85% ± 9. Mean platelet life span was 146 hr ± 13. Correcting for plasma radioactivity (always less than 3.5%) did not significantly affect the estimate of platelet life span (145 hr ± 16) or recovery (85% ± 12). Platelet survival estimates, repeated at different times, were reproducible. In 5 baboons, platelets were also harvested by a single step differential centrifugation. The mean life span of a representative platelet population was significantly longer than that of platelets harvested by a single step. Recovery values of the representative and non-representative population were similar. We conclude that it may be important to harvest and label a fully representative platelet population for kinetic studies. The proposed method is simple and reproducible, and may be applied in studies in humans.
Keywords: Indium-111; Primates; In-lll-labelled platelets; Platelet labelling technique; Blood platelets